Expand 2/5(−5c+10)

5 answers

To expand the expression \( \frac{2}{5}(-5c + 10) \), we will distribute \( \frac{2}{5} \) to both terms inside the parentheses.

  1. Distribute \( \frac{2}{5} \) to \(-5c\): \[ \frac{2}{5} \times -5c = -\frac{2 \times 5c}{5} = -2c \]

  2. Distribute \( \frac{2}{5} \) to \(10\): \[ \frac{2}{5} \times 10 = \frac{2 \times 10}{5} = \frac{20}{5} = 4 \]

Now, combine the results from both distributions: \[ -2c + 4 \]

Thus, the expanded expression is: \[ -2c + 4 \]

Expand −7/6(3g+2)

To expand the expression \( -\frac{7}{6}(3g + 2) \), we will distribute \( -\frac{7}{6} \) to both terms inside the parentheses.

  1. Distribute \( -\frac{7}{6} \) to \( 3g \): \[ -\frac{7}{6} \times 3g = -\frac{7 \times 3g}{6} = -\frac{21g}{6} = -\frac{7g}{2} \quad \text{(simplified)} \]

  2. Distribute \( -\frac{7}{6} \) to \( 2 \): \[ -\frac{7}{6} \times 2 = -\frac{7 \times 2}{6} = -\frac{14}{6} = -\frac{7}{3} \quad \text{(simplified)} \]

Now, combine the results from both distributions: \[ -\frac{7g}{2} - \frac{7}{3} \]

Thus, the expanded expression is: \[ -\frac{7g}{2} - \frac{7}{3} \]

So what’s the answer

The expanded form of the expression \(-\frac{7}{6}(3g + 2)\) is:

\[ -\frac{7g}{2} - \frac{7}{3} \]

This is the final answer. If you would like to combine the terms or write it in a different format, please let me know!